Os Reflexos Financeiros e Organizacionais do Planejamento Estratégico em Igrejas Cristãs - Ribeiro, Antonio Fernando Simões (2024)
This dissertation analyzes the financial, budgetary and organizational consequences arising from the implementation of strategic planning in Christian churches, focusing on congregations located in the city of Cascavel/PR. The central objective of the research was to investigate how these religious organizations structure and manage their financial and budgetary resources based on their organizational strategies, considering their short and long-term institutional goals. The research was conducted based on three specific objectives: (1) analyze the clarity and specificity of churches' mission and vision statements, evaluating their direct impact on the formulation of financial and budgetary plans; (2) verify the level of involvement of members and collaborators in the strategic planning process and its effects on the efficiency of budget control and financial sustainability; and (3) examine the use of strategic management tools, such as SWOT and 5W2H, for monitoring and executing financial strategies in churches. The study adopted a qualitative approach, using semi-structured interviews carried out with leaders and members of the congregations. Data analysis was carried out with the aid of the IRAMUTEQ software, which allowed the identification of relevant patterns related to financial governance, budget control practices and the implementation of strategic management tools. The results demonstrate that, although churches recognize the relevance of strategic planning, the operationalization of this planning presents challenges, especially with regard to the management of financial resources and the absence of systematic control tools. It was observed that most churches have generic mission and vision statements, without specific developments for monitoring financial goals, which compromises the ability to plan in the long term. Furthermore, a centralization of strategic and financial decisions by leaders was identified, with low participation of members and collaborators in decision-making processes, compromising effectiveness in budget execution and monitoring. Given these findings, the dissertation presents recommendations aimed at improving strategic planning in the churches studied: (1) restructuring mission and vision statements, so that they guide the development of clear financial goals and detailed budget plans; (2) expanding the participation of congregation members in governance and financial control processes, promoting greater transparency and coresponsibility; and (3) training leaders and employees in the use of strategic management tools, such as SWOT analysis and the 5W2H method, to improve the continuous monitoring of goals and financial results. It is concluded that, despite the recognition of the importance of strategic planning, its implementation, especially in the financial and budgetary context, still requires more robust systematization and more rigorous monitoring. The research contributes to the field of accounting by highlighting the relationship between financial governance, strategic planning and organizational sustainability in the context of Christian churches, proposing as a future research agenda the exploration of methodologies that integrate the particularities of these organizations with advanced financial management practices and finance.